Estudio clínico comparativo de restauraciones oclusoproximales con amalgama tase dispersa y restauraciones oclusoproximales con resina compuesta - Lahoud S., Wíctor (2005)
The objetive of the study was to evaluate the clinical performance of restaurations oclusoproxiamles withresin.was selections60 bicupids and molars with diagnostic of caries not compromisepulp divided into 2 groups: Group I 30 for restoration with amalgam fase dispersa,group II 30 for restoration with resins. Evaluated in each restoration: surface texture, resistence, marginal adapation, secundary caries and sensibility. The results showeds 100% success after of 12 moths ofin 60 treatedcases.